Competitiveness of Indonesian Livestock Production among ASEAN Countries - Tjeppy D Soedjana; Atien Priyanti (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2017)
ASEAN is one of the fastest growing regional economic communities and its combined human population of around 600 million people. Heterogeneity of ASEAN member countries includes population size, cultural background, structure and development of the economy, and level of income. Agriculture is well known as one of the key engine of economic growth of the ASEAN member countries, seen from the fact that most of the countries in this region are strongly depend on this sector including animal production. The purpose of this paper is to discuss the competitiveness of Indonesian production costs of selected livestock products compared to other ASEAN member countries. The following member countries are at their first rank or competitiveness status for the livestock and poultry commodities, namely Cambodia for beef cattle, Malaysia for pigs, the Philippines for sheep and goats, and Thailand for broiler chickens. Indonesia with the highest poultry population in the region, compared to Thailand, Malaysia, and the Philippines has not yet performed as that good in terms of production costs. The position of Indonesia based on production cost was at the fourth rank for beef, third for sheep and goat, and fourth for broiler compared to other ASEAN member countries. Therefore, Indonesia should improve the efficiency production of livestock and poultry to achieve better competition status.